1995
DOI: 10.1093/jac/36.suppl_a.121
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute bacterial exacerbations of chronic obstructive pulmonary disease in hospitalised patients -- a comparison of meropenem and imipenem/cilastatin

Abstract: Meropenem and imipenem/cilastatin were compared in an open, randomised prospective multicentre study in the treatment of acute exacerbations of severe chronic obstructive pulmonary disease in hospitalised patients. One-hundred-and-seventy-three patients were enrolled; 164 were evaluable for clinical efficacy and 98 for bacteriological efficacy, with 144 pathogens isolated. The predominant pathogens were Haemophilus influenzae (n = 30), Streptococcus pneumoniae (18), Staphylococcus aureus (12), Pseudomonas aeru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…In a clinical trial (5) comparing the efficacy of meropenem and imipenem for the treatment of acute bacterial exacerbations of COPD, the superinfection rate of imipenem treatment was only one in 37 patients, much lower than in our study. In our study population, the mean Pco 2 was 69.9 ± 24.1 mmHg, and 35.3% of patients received invasive mechanical ventilation.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In a clinical trial (5) comparing the efficacy of meropenem and imipenem for the treatment of acute bacterial exacerbations of COPD, the superinfection rate of imipenem treatment was only one in 37 patients, much lower than in our study. In our study population, the mean Pco 2 was 69.9 ± 24.1 mmHg, and 35.3% of patients received invasive mechanical ventilation.…”
Section: Discussioncontrasting
confidence: 80%
“…For patients critically ill with acute respiratory failure due to severe COPD, especially those attacked by gram‐negative enteric bacilli producing extended‐spectrum beta‐lactamase (ESBL), imipenem treatment is reasonable and critical. Imipenem has been proved to be efficacious and safe by many randomised multicentre studies in the treatment of hospitalised patients with pneumonia and COPD (4–6). Despite great advances in antimicrobial chemotherapy and supportive care, acute exacerbations of severe COPD and associated acute respiratory failure remain a major practical therapeutic challenge for respiratory intensive care specialists.…”
mentioning
confidence: 99%
“…Imipenem versus meropenem: Comparisons of imipenem versus meropenem for respiratory tract infections are limited to acute bacterial exacerbations of chronic obstructive pulmonary disease. Although Hamacher et al (68) reported "cure or improvement" rates greater than 95% with either antibiotic, the authors absolutely do not recommend the use of either carbapenem for acute exacerbations of chronic bronchitis.…”
Section: Respiratory Tract Infectionsmentioning
confidence: 97%
“…Four trials reported seizures with rates ranging from 1.1-6%. [34][35][36][37] A total of 1661 patients received imipenem-cilastatin therapy, with 25 patients experiencing seizure activity. Of the 25 patients experiencing seizures, eight had risk factors: history of meningitis (one patient), history of seizures (one patient), and traumatic brain injury (six patients).…”
Section: Imipenem-cilastatinmentioning
confidence: 99%